Availability of Chinook and sockeye salmon as prey to Cook Inlet beluga whales - Jordy Bernard; Bill Templin; Adam Reimer; Timothy McKinley; Kalin Kellie; Kate Lomac-MacNair; Megan Blees; Morgan Bender; Milo Adkison; Lori Polasek; Lori Quakenbush (Frontiers in Marine Science, 2026)
Cook Inlet beluga whales (CIBW) are an endangered population of toothed whales in southcentral Alaska that have not shown signs of recovery over the past two decades. Since the 1999 harvest moratorium, the number of whales in the population has remained relatively stable, with the 2022 estimate at 381 whales. Despite extensive research efforts since its Endangered Species Act listing in 2008, the mechanisms limiting population growth remain poorly understood. Recent studies suggest prey availability could be a significant factor limiting reproduction. This study provides information relating to CIBW prey availability and identifies mechanisms that may limit CIBW population growth. We developed a database containing decades of Cook Inlet fisheries data collected by the Alaska Department of Fish and Game. We used annual run size and fish size data to establish indices of Chinook ( Oncorhynchus tshawytscha) and sockeye salmon ( Oncorhynchus nerka ) availability within the Northern and Central Districts of Upper Cook Inlet. Data were not available to do the same for chum ( Oncorhynchus keta ), coho ( Oncorhynchus kisutch ), and pink salmon ( Oncorhynchus gorbuscha ) or for other important prey species, such as eulachon ( Thaleicthys pacificus ) and Pacific herring ( Clupea pallasii ), thus we focus on prey species Chinook and sockeye salmon. Here we summarize fisheries information archived in the database, estimate annual vital rates of CIBWs using an age-structured integrated population dynamics model, and correlate these vital rates to indices of prey availability (i.e., the annual biomass of select salmon runs based on available fisheries data). The biomass of Chinook salmon, the first species of salmon to arrive in Cook Inlet to spawn, declined significantly in the late 2000s. However, the biomass of other species, including sockeye salmon, has shown no clear trend since the 1980s. There were some indications that CIBW survival rates declined between 2005 and 2017, a period over which the biomass of Chinook and sockeye runs decreased in magnitude. However, it is not clear without additional information, such as a longer time series on CIBW survival rates and prey abundance, whether an increase in salmon availability would lead to an increase in CIBW population.

Consensus Guidelines for Advancing Coral Holobiont Genome and Specimen Voucher Deposition - Christian R. Voolstra; Kate M. Quigley; Sarah W. Davies; John Everett Parkinson; Raquel S. Peixoto; Manuel Aranda; Andrew C. Baker; Adam R. Barno; Daniel J. Barshis; Francesca Benzoni; Victor Bonito; David G. Bourne; et al. (Frontiers in Marine Science, 2021)
Coral research is being ushered into the genomic era. To fully capitalize on the potential discoveries from this genomic revolution, the rapidly increasing number of high-quality genomes requires effective pairing with rigorous taxonomic characterizations of specimens and the contextualization of their ecological relevance. However, to date there is no formal framework that genomicists, taxonomists, and coral scientists can collectively use to systematically acquire and link these data. Spurred by the recently announced “Coral symbiosis sensitivity to environmental change hub” under the “Aquatic Symbiosis Genomics Project” - a collaboration between the Wellcome Sanger Institute and the Gordon and Betty Moore Foundation to generate gold-standard genome sequences for coral animal hosts and their associated Symbiodiniaceae microalgae (among the sequencing of many other symbiotic aquatic species) - we outline consensus guidelines to reconcile different types of data. The metaorganism nature of the coral holobiont provides a particular challenge in this context and is a key factor to consider for developing a framework to consolidate genomic, taxonomic, and ecological (meta)data. Ideally, genomic data should be accompanied by taxonomic references, i.e., skeletal vouchers as formal morphological references for corals and strain specimens in the case of microalgal and bacterial symbionts (cultured isolates). However, exhaustive taxonomic characterization of all coral holobiont member species is currently not feasible simply because we do not have a comprehensive understanding of all the organisms that constitute the coral holobiont. Nevertheless, guidelines on minimal, recommended, and ideal-case descriptions for the major coral holobiont constituents (coral animal, Symbiodiniaceae microalgae, and prokaryotes) will undoubtedly help in future referencing and will facilitate comparative studies. We hope that the guidelines outlined here, which we will adhere to as part of the Aquatic Symbiosis Genomics Project sub-hub focused on coral symbioses, will be useful to a broader community and their implementation will facilitate cross- and meta-data comparisons and analyses.

The Impact of Federal and State Conservation Programs on Farmer Nitrogen Management - Adam P. Reimer; Riva C. H. Denny; Diana Stuart (Environmental Management, 2018)

Farmer Participation in U.S. Farm Bill Conservation Programs - Adam P. Reimer; Linda S. Prokopy (Environmental Management, 2014)